Peru: some considerations on the fiscal sector between 1884 and 1912 - Armas A., Fernando (2000)
This article tries to renew the debate on a particular period in the economic history of Peru and emphasizes on some historiographic errors on its understanding. More specifically, it points that between 1888 and 1892 the Peruvian exterior commerce grew and that on 1912 some economic indicators showed the same level they had on the 1870 decade. This fact marked an important inflection point that needs to be noticed.